Expression of pro- and anti-inflammatory cytokines during anti-proprotein convertase subtilisin/kexin type 9 therapy in patients with statin-resistant familial hypercholesterolemia - Morales-Portano, Julieta Danira; Trujillo-Cortés, Rafael; Roa-Martínez, Bricia Margarita; Pérez-Cabeza de Vaca, Rebeca; García, Silvia; Mondragón-Terán, Paul; Suárez-Cuenca, Juan A. (Frontiers in Cardiovascular Medicine, 2024)
Background Some clinical dyslipidemia cases do not respond to statins, known as statin-resistant familial hypercholesterolemia (SR-FH), in which patients are under a high cardiovascular risk despite statin therapy. Therefore, novel therapeutic alternatives are required. Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) reduce cholesterol levels and cardiovascular disease risk, particularly in patients with SR-FH, where PCSK9i may differentially affect pro- and anti-inflammatory mediators depending on the clinical setting. Aim To evaluate the effect of PCSK9i treatment on pro- and anti-inflammatory cytokines in patients with SR-FH. Methods Before–after comparison, quasi-experimental, single-center study in patients with SR-FH. Blood samples were processed to obtain complete blood counts of glycated hemoglobin and serum lipid levels. Flow cytometry was performed to characterize baseline circulating M1- and M2-macrophages and monocytes. Multiplexing of plasma samples was used to compare plasma fraktaline, interleukins (ILs), monocyte chemoattractant protein-1 (MCP-1), and tumor necrosis factor (TNF)-alpha. The endpoints were lower serum lipid levels and pro-inflammatory mediator modification. Results Twenty patients with SR-FH, aged 58 years and most of them males, were included, with a mean body–mass index of 26.4 and showing ischemic heart disease and similar values of baseline M1- and M2-macrophages and monocytes. Six-month iPSCK-9 therapy considerably reduced LDLc, increased anti-inflammatory cytokine (IL-4), and modified pro-inflammatory cytokine (TNF-alpha and MCP-1) levels. No notable effects were observed for the other markers. Conclusion PCSK9i therapy exerted subclinical anti-inflammatory and anti-atherogenic effects, indicating potential benefits for clinical outcomes.